Draft Genome Sequence of Pseudomonas stutzeri Strain KMS 55, an Endophytic Diazotroph Isolated from Rice Roots - Annapurna, Kannepalli (Genome Announc, 2017)
Pseudomonas stutzeri strain KMS 55 (MTCC 12703) is an isolate from the root tissues of rice (Oryza sativa L.) that displays a high biological nitrogen fixation ability. Here, we report the complete genome sequence of this strain, which contains 4,637,820 bp, 4,289 protein-coding genes, 5,006 promoter sequences, 62 tRNAs, a single copy of 5S-16S-23S rRNA, and a genome average GC content of 51.18%. Analysis of the ~4.64-Mb genome sequence will give support to increased understanding of the genetic determinants of host range, endophytic colonization behavior, endophytic nitrogen fixation, and other plant-beneficial roles of Pseudomonas stutzeri.